Can Administration of Potentized Homeopathic Remedy, Arsenicum Album, Alter Antinuclear Antibody (ANA) Titer in People Living in High-Risk Arsenic Contaminated Areas? I. A Correlation with Certain Hematological Parameters. Issue 1 (2006) - Belon, Philippe; Banerjee, Pathikrit; Choudhury, Sandipan Chaki; Banerjee, Antara; Biswas, Surjyo Jyoti; Karmakar, Susanta Roy; Pathak, Surajit; Guha, Bibhas; Chatterjee, Sagar; Bhattacharjee, Nandini; Das, Jayanta Kumar; Khuda-Bukhsh, Anisur Rahman
Abstract : To examine whether elevated antinuclear antibody (ANA) titers reported in random human population of arsenic contaminated villages can be reverted to the normal range by administration of a potentized homeopathic drug, Arsenicum album, randomly selected volunteers in two arsenic contaminated villages and one arsenic-free village in West Bengal (India) were periodically tested for their ANA titer as well as various blood parameters in two types of experiments: 'placebo-controlled double blind' experiment for shorter duration and 'uncontrolled verum fed experiment' for longer duration. Positive modulation of ANA titer was observed along with changes in certain relevant hematological parameters, namely total count of red blood cells and white blood cells, packed cell volume, hemoglobin content, erythrocyte sedimentation rate and blood sugar level, mostly within 2 months of drug administration. Thus, Arsenicum album appears to have great potential for ameliorating arsenic induced elevated ANA titer and other hematological toxicities.